2017
DOI: 10.1097/j.pain.0000000000000940
|View full text |Cite
|
Sign up to set email alerts
|

Effects of acute psychological stress on placebo and nocebo responses in a clinically relevant model of visceroception

Abstract: There is evidence to suggest a role of emotions in placebo and nocebo effects, but whether acute psychological stress changes the magnitude of placebo or nocebo responses has not been tested. In a clinically relevant model of visceroception, we assessed effects of acute psychological stress on changes in urgency and pain in response to positive or negative treatment suggestions. In 120 healthy volunteers, perceived urge-to-defecate and pain in response to individually calibrated rectal distensions were measure… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
52
1
3

Year Published

2018
2018
2024
2024

Publication Types

Select...
4
3

Relationship

3
4

Authors

Journals

citations
Cited by 41 publications
(61 citation statements)
references
References 59 publications
5
52
1
3
Order By: Relevance
“…Importantly, symptom burden in patients is often not limited to pain, but also involves defecatory urgency as a highly troublesome symptom in a broad range of GI conditions (12)(13)(14). Psychological modulation of defecatory urgency has previously been proposed (15), and our own recent data suggested that acute stress amplified nocebo effects especially for the symptom of distension-induced urgency more so then the symptom of pain in healthy volunteers (16). While together these findings clearly support a role of acute as well as chronic stress in different dimensions of visceroception, experimental work particularly on effects of chronic stress remains scarce.…”
Section: Introductionmentioning
confidence: 88%
See 3 more Smart Citations
“…Importantly, symptom burden in patients is often not limited to pain, but also involves defecatory urgency as a highly troublesome symptom in a broad range of GI conditions (12)(13)(14). Psychological modulation of defecatory urgency has previously been proposed (15), and our own recent data suggested that acute stress amplified nocebo effects especially for the symptom of distension-induced urgency more so then the symptom of pain in healthy volunteers (16). While together these findings clearly support a role of acute as well as chronic stress in different dimensions of visceroception, experimental work particularly on effects of chronic stress remains scarce.…”
Section: Introductionmentioning
confidence: 88%
“…The top and bottom tertile were chosen to define participants with low and elevated perceived chronic stress, as detailed below, and included in the current analysis. Participants had been recruited through local advertisements for the primary study on the modulation of placebo and nocebo effects by acute experimental stress (16) or relaxation (17) in visceral pain. They had been informed that the aim of the study would be to investigate psychological mechanisms underlying effects of different drugs on experimentally-induced visceral symptoms.…”
Section: Participantsmentioning
confidence: 99%
See 2 more Smart Citations
“…Studies were conducted in the same experimental setting and with identical methodology for visceral sensitivity testing (see below). Participants for both studies had been recruited via local advertisement using the same inclusion and exclusion criteria for participation in a study on effects of stress or relaxation and on effects of oral hydrocortisone on visceral pain . Please note that visceral sensitivity measures used herein were acquired in both studies before volunteers were randomized to subsequent experimental manipulations (ie, they constituted baseline measures in the primary studies).…”
Section: Methodsmentioning
confidence: 99%